The Earnings and Employment of Community Colleges’ Graduates: Occupational Field and Gender Analysis - Zurani Buang; M M Mohamad; A Ahmad; N Yuniarti (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
Community College Malaysia is one of the Technical Education and Vocational Training Institutions in the country that plays an important role in steering the country's aspirations to become a developed nation by 2020. It focuses mainly on the supply of human capital among the youth future worker fit with skills, competencies and efficient industry requirements. However, the income earned varies widely based on the industry's ability to provide employment. The income factors led to an increase or decrease in the number of graduates' employability. There are more than ten categories of programs offered by community colleges and the numbers of employability relating to the demand from industries providing job opportunities to skilled workers. Therefore, this study aims to conduct a descriptive analysis of the earnings and employment of Community Colleges graduates based on occupational field and gender. The data were obtained by the survey of Community Colleges graduates in 2018. The study population consisted of 7725 graduates and 367 respondents were involved as samples who answered their respective job status in graduate's employability survey provided by the ministry. The result shows that most respondents received a salary between RM1501-RM2000, while the rest of the graduates earned between RM1001-RM1500 and RM1001-RM1500. In the gender factor of employment, female graduates exceed compared to male graduates on the income scale of RM1000 and below. However, at higher income levels of RM1501-2000 and above, male graduates earn more than their counterparts, the female graduates. The findings of this study are expected to be a future guide and encouragement, especially for community colleges to study skill programs that are in line with industry requirements and produce a competent and dynamic human capital to enhance the country's economy.